Rare Case of Large Bowel Injury due to Direct Blunt Trauma to a Preexisting Femoral Hernia - C. Tinner; M. Odermatt; P. Villiger (Case Reports in Surgery)
We report a case of an 85-year-old man with a known asymptomatic left femoral hernia who was admitted to the emergency ward a few hours after falling from a bicycle and suffering from blunt trauma of the handlebar to the left inguinal region. The clinical findings and a computed tomography (CT) scan detecting free air in the femoral hernia sac suggested bowel perforation. Emergency laparotomy 6 hours after the incident confirmed a tear of the sigmoid colon accompanied by free blood and faeces in the left inguinal region of the abdomen. A segmental sigmoid resection and a primary end-to-end colorectal anastomosis were performed. The postoperative course was complicated by delayed oral feeding, a local infection, and a partial left testicle necrosis that led to secondary resection. The patient was discharged after 32 days of in-hospital care. Three months post trauma, we recorded a restitutio ad integrum. The case exemplifies that blunt trauma to preexisting femoral hernias may cause potentially lethal bowel perforation and that the time interval between time of injury and surgical treatment may be a prognostic factor. CT scans seem most suitable for ruling out bowel perforation. The scarce literature for blunt trauma to hernias is reviewed.